BIODIVERSITY OF ANGIOSPERMS IN SUMBERAWAN TEMPLE, SINGOSARI, MALANG DISTRICT - Tunazjah, Savina; Zahrani, Ifta Alifia; Nisa, Khoirun; Maulida Dewi, Siti Zulaika; Prasetya, Akmal Rizky; Nabila, Irbah Jihan; Manggalgita, Cornellia Wening; Fardhani, Indra (Universitas Medan Area, 2024)
Sumberawan Temple is a tourist area that is inextricably linked to diversity of plants. One of them is angiosperm plants. Angiosperms occupy about 90% of all plant species and have 250,000 species. The objective of this study is to determine the biodiversity of angiosperm plants in Sumberawan Temple area which is located in Singosari, Malang Regency. The research method used was vegetation analysis using a single plot measuring 20 x 20 m2. The shape of the plot used wass square with an area of ​​400 m2. There were 12 types of angiosperm plant species in 9 different families. To determine the species richness index using the Margalef index, the diversity index using the Shannon Weinner index and the evenness index using the Evenees index. The findings indicated that species richness was in the low category, diversity and evenness were in the high category. It is due to the fewer species in the area but the greater variety of species in Sumberawan Temple area. The diversity of species indicates the number of species that coexist.